Constraining the age of the last marine sediments in the late Cretaceous of central south Pyrenees (NE Spain): Insights from larger benthic foraminifera and strontium isotope stratigraphy. (January 2016) - Caus, Esmeralda; Frijia, Gianluca; Parente, Mariano; Robles-Salcedo, Raquel; Villalonga, Raquel
Abstract: The uppermost Cretaceous (upper Campanian–Maastrichtian) marine deposits of the central south Pyrenees host a rich larger benthic foraminiferal fauna and several rudist-rich levels. These marine deposits are directly overlain by the continental facies of the Arén and Tremp Formations, which are famous for their fossil dinosaur remains. Larger benthic foraminiferal distribution documents an important faunal turnover in all the carbonate platform environments within the photic zone, from open marine to littoral areas. Biostratigraphy indicates that this turnover occurred close to the Campanian-Maastrichtian boundary. This is also confirmed by strontium isotope stratigraphy which indicates an earliest Maastrichtian age for the appearance of the larger benthic foraminiferal assemblage constituted by Lepidorbitoides socialis, Clypeorbis mammillata, Wannierina cataluniensis, Orbitoides gruenbachensis, Siderolites aff. calcitrapoides, Fascispira colomi, Omphalocyclus macroporus and Laffiteina mengaudi . In particular, a numerical age of 71 Ma is obtained for the Hippurites radiosus level, just a few meters below the first continental deposits of the Arén sensu stricto Formation. The youngest marine sediments of the central south Pyrenees are early Maastrichtian in age. This is also an important constraint for the age of the end-Cretaceous dinosaur fossil localities of the Tremp basin. Highlights: Larger foraminifera turnover in S-Pyrenees around Campanian-Maastrichtian boundary. The last marine sediments are early Maastrichtian (biostratigraphy and Sr isotopes). A 71 Ma Sr isotopes age for the H. radiosus horizon, few meters below the Arén s.s.